Kiskenimisowin (self-knowledge): Co-researching Wellbeing With Canadian First Nations Youth Through Participatory Visual Methods - Victor, Janice; Linds, Warren; Episkenew, Jo-Ann; Goulet, Linda; Benjoe, Dustin; Brass, Dustin; Pandey, Mamata; Schmidt, Karen (NEIHR National Coordinating Centre, 2016)
Indigenous youth represent one of the most marginalized demographics in Canada. As such they must contend with many barriers to wellness that stem from oppression, including historical and ongoing colonization and racism. Developing effective health programming requires innovation and flexibility, especially important when programs take place in diverse Indigenous communities where local needs and cultural practices vary. This article reports the findings of an after-school program in 2014 that blended a participatory visual method of research with Indigenous knowledge, methodologies, and practices to provide sociocultural health programming for youth in a First Nation in southern Saskatchewan, Canada. Engaging with youth to co-research wellbeing through the arts was conceptualized as both research and health promotion. Participatory arts methods created a safe space for youth to express their views of health and wellness issues while developing self-knowledge about their individual and cultural identities.